Skeletal Muscle Myofibers Directly Contribute to LPS-Induced Systemic Inflammatory Tone - Bivona III, Joseph J.; Mank, Madeleine M.; Stapleton, Renee D.; Files, D. Clark; Toth, Michael J.; Poynter, Matthew E. (Frontiers in Pharmacology, 2022)
The abundance, anatomical distribution, and vascularity of skeletal muscle make it a potentially important contributor to local cytokine production and systemic cytokine abundance during inflammatory events. An orchestrated balance between the production of pro- and anti-inflammatory mediators is necessary for proper immune function, yet the contribution of the body’s largest organ system to this process is largely unknown. Endotoxin (lipopolysaccharide, LPS) stimulates toll-like receptor-4 (TLR4) to induce the production of several pro-inflammatory cytokines, including interleukin-6 (IL-6) and C-C motif chemokine ligand 2 (CCL2), by a of myriad cell types. We sought to quantify the influence of skeletal muscle myocytes on systemic cytokine levels following an acute endotoxemia challenge. To accomplish this, we generated muscle specific conditional knockouts for TLR4 (TLR4SMKO), IL-6 (IL6SMKO), and CCL2 (CCL2SMKO). We administered low levels of intravenous lipopolysaccharide (IV LPS) to these receptor and effector knockout mice and collected samples after three hours. Using gene expression analysis of gastrocnemius muscle and cytokine measurements of serum, we determined that deletion of skeletal myocyte IL-6 or CCL2 led to a 93% and 57% reduction of these specific cytokines in the systemic circulation, respectively. Skeletal myocyte specific TLR4 deletion decreased the expression of CCL2, CXCL1, and IL-6 in the gastrocnemius muscle. These data indicate the critical involvement and direct contribution of skeletal muscle myocytes during the early systemic inflammatory cytokine response to endotoxin.